Heterologous expression and characterization of L-asparaginase from marine Photobacterium sp. strain J15 - Yaacob, Mohd Adilin (2014)
L-asparaginase catalyzes the conversion of the L-asparagine to L-aspartate and ammonia. Although L-asparaginase is one of the main components used in chemotherapy, toxicity problem associated with glutaminase activity of commercial asparaginase products such as Elspar, oncaspar and Erwinaze derived from Escherichia coli and Erwinia crysanthemi becomes a major limitation in cancer treatment. The aim of the current study is to isolate L-asparaginase (J15 asparaginase) gene from Photobacterium sp. strain J15 and characterize J15 asparaginase biochemically by molecular expression and in silico modeling. Genome mining revealed an open reading frame of 1011 bp coding for J15 asparaginase gene from halo-tolerant Photobacterium sp. strain J15. The J15 asparaginase gene was isolated by using specific primer flanking the full length of gene overexpressed in pET-32b vector and transformed into E. coli strain Rosetta-gami B (DE3) pLysS. The J15 asparaginase was purified to homogeneity by using two-step chromatographic: Ni2+-Sepharose affinity chromatography and Q-Sepharose anion exchange chromatography. The final specific activity and yield of the enzyme achieved from these steps were 20 U/mg and 49.2 %, respectively. The functional dimeric form of J15-asparaginase with molecular weight of ~70 kDa was characterized. The optimum temperature and pH was at 25 °C and pH 7 respectively. It was stable in the presence of 1 mM Ni2+ and Mg2+, but was inhibited by Mn2+, Fe3+ and Zn2+. J15 asparaginase actively hydrolyzed its natural substrate Lasparagine,but had low activity towards L-glutamine. The Tm for J15 asparaginase was about 51 °C, as revealed by denatured protein analysis of Circular Dichorism (CD) spectra. The Km, Kcat, Kcat/Km of J15 asparaginase was 0.76 mM, 3.2 S-1, and 4.21 S-1mM-1, respectively. Structural analysis of J15 asparaginase was analysed by homology modeling and Molecular Dynamic (MD) simulations. The J15 asparaginase model was validated by using Ramachandran plot, and ERRAT 2.0. The monomer of J15 asparaginase comprises of 31 % α-helixs and 18.3 % ß-sheet. RMSD value of 0.436 with 76.85 % identities was recorded when the J15 asparaginase superimposed with template (pdb: 2OCD). MD simulation for 10 ns was carried out to examine conformational changes of J15-asparaginase structure at different temperatures (25 °C, 45 °C, and 65 °C) and it was found that at 25 °C, J15 asparaginase was most stable hence able to hydrolyze the substrate at optimum rate. The function of mobile lid-loop at the active site was analyzed by using MD simulation at 10 ns. Tyr24, His 22, Gly23, Val25, and Pro26 residues might directly involve in ‘open’ and ‘closed’ of lid-loop conformation to facilitate the conversion of substrate during enzymatic reaction. Low glutaminase activity possessed by J15 asparaginase might serve as an ideal candidate to be used as enzyme-drug in cancer treatment.